Graph-based approaches for analyzing team interaction on the example of soccer - Brandt, M.; Brefeld, U. (Machine Learning and Data Mining for Sports Analytics ECML/PKDD 2015 workshop, 2015)
We present a graph-based approach to analyzing player interaction in team sports. A simple pass-based representation is presented that is subsequently used together with the PageRank algorithm to identify the importance of the players. Aggregating player scores to team values allows for turning our approach into a predictor of the winning team. We report on empirical results on five German Bundesliga seasons.